The Implementation of Akhlak-Based Al-Islam Learning in Developing Students’ Anti- bullying Character at SMA Muhammadiyah 4 Jakarta - Valiha Zulkarnaini, Siti Nur; Purwidianto, Purwidianto (UIR Press, 2026)
This study aims to examine and analyze the implementation of akhlak-based Al-Islam learning in shaping students’ anti-bullying character at SMA Muhammadiyah 4 Jakarta. This study applies a descriptive qualitative approach to obtain an in-depth understanding of the learning process and character formation among students. Data were collected through observation, in-depth interviews, and documentation involving Al-Islam teachers, guidance and counseling teachers, students, and the school principal. The findings indicate that akhlak-based Al-Islam learning plays an important role in fostering students’ awareness, empathy, and positive social behavior oriented toward antibullying attitudes. The implementation of learning is carried out through teachers’ exemplary behavior, habituation of moral values, contextual learning, as well as support from school policies and counseling services. These efforts contribute to reducing verbal and nonverbal bullying behavior and creating a safe, religious, and conducive school environment. This study concludes that akhlak-based Al-Islam learning is an effective approach to developing students’ antibullying character and fostering a conducive and morally grounded school environment.